2018
DOI: 10.1002/adfm.201802581
|View full text |Cite
|
Sign up to set email alerts
|

Thickness‐Dependent Carrier Transport Characteristics of a New 2D Elemental Semiconductor: Black Arsenic

Abstract: 2D elemental layered crystals, such as graphene and black phosphorus (B-P), have received tremendous attentions due to their rich physical and chemical properties. In the applications of nanoelectronic devices, graphene shows super high electronic mobility, but it lacks bandgap which impedes development in logical devices. As an alternative, B-P shows high mobility of up to about 1000 cm 2 V −1 s −1 . However, B-P is very unstable and degrades rapidly in ambient conditions. Orthorhombic arsenic (black arsenic;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
182
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(190 citation statements)
references
References 53 publications
3
182
0
Order By: Relevance
“…As a cousin of black phosphorene, black arsenic (b‐As) has just been fabricated and shows interesting anisotropic transport behaviors in electrical and thermal properties . Its puckered atomic structure, shown in Figure d, is similar to that of black phosphorene.…”
Section: Thermal Properties In 2d Semiconductorsmentioning
confidence: 99%
“…As a cousin of black phosphorene, black arsenic (b‐As) has just been fabricated and shows interesting anisotropic transport behaviors in electrical and thermal properties . Its puckered atomic structure, shown in Figure d, is similar to that of black phosphorene.…”
Section: Thermal Properties In 2d Semiconductorsmentioning
confidence: 99%
“…Both theoretical and experimental characterization have demonstrated that B‐As is a layered material similar to B‐P, and the band structure is related to the number of layers. The bulk B‐As bandgap is about 0.3 eV, which is a direct bandgap; the single layer is about 1.5 eV, which is an indirect bandgap . Most importantly, B‐As has a stronger anisotropy .…”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 98%
“…Previous work has shown that pure B‐As is metastable, so it can be only stabilized by impurities (such as B‐AsP), which is why the content of As in B‐AsP can only reach 0.83 . It is difficult for the laboratory to synthesize B‐As, but there are natural minerals of B‐As in nature . Both theoretical and experimental characterization have demonstrated that B‐As is a layered material similar to B‐P, and the band structure is related to the number of layers.…”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations